THE IMPORTANCE OF USING LOGICAL METHODS IN DEVELOPING STUDWNTS` KEY COMPETENCIES IN BIOLOGY LESSONS - Jumaniyozova N. X. (PhD) (Modern American Journals, 2025)
This article discusses the content of the formation of subject competencies in students along with key competencies based on the curriculum in biology
Keywords: Biological education, competencies, key competencies, subject competencies